Smoking reduction interventions for smoking cessation - Lindson, N; Klemperer, E; Hong, B; Ordóñez-Mena, J; Aveyard, P (Cochrane Collaboration, 2019)
Background: The standard way most people are advised to stop smoking is by quitting abruptly on a designated quit day. However, many people who smoke have tried to quit many times and may like to try an alternative method. Reducing smoking behaviour before quitting could be an alternative approach to cessation. However, before this method can be recommended it is important to ensure that abrupt quitting is not more effective than reducing to quit, and to determine whether there are ways to optimise reduction methods to increase the chances of cessation.